Melaksanakan Bimbingan Berbasis KKG sebagai Upaya Meningkatkan Kompetensi Guru Kelas dalam Penyusunan RPP Berkarakter di SDN 46 Mataram - Jamilan, Jamilan (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
Background The holding of this research is the low competence of the target teacher In SD Negeri 46 Mataram in the preparation of Learning Implementation Plan (RPP) Based on KTSP that have less confidence in the learning process. The solution is provided assistance both groups and individuals in the preparation of RPP based on KTSP. The aim is to know the effectiveness of KKG-based mentoring activities in order to improve teacher competence in preparing RPP based on KTSP, which is useful to improve professionalism as principal and for teachers to improve the learning process in the classroom. This study was conducted in two cycles, each cycle twice a meeting. The stages of each cycle are planning, execution, observation, and reflection. The indicators of success in this study are; 1) the results of principal observation and teacher observation during the mentoring process has obtained the average score> 4.0, 2) teacher work in the preparation of RPP reach> 85% with the average value> 80.00. The result of the research in cycle I was observed by the principal average (3.40), average teacher observation (3.33) and average individual work result value (68,78) with percentage of achievement (0%). In cycle II the mean principal observation (4.10), average teacher observation (4.50) and average individual work result value (87,50) with percentage of achievement (100%). The success indicator has been reached, the research stated successful and stopped in cycle II. Conclusion; the implementation of assistance can improve the competence of the target teachers of SD Negeri 46 Mataram in the preparation of RPP based on KTSP. It is recommended that other Principals conduct similar research in an effort to increase the competence of teachers, and to subject teachers to be able to develop RPP based on KTSP.